Giant thermal expansion and α-precipitation pathways in Ti-alloys - Matthias Bönisch (Nature Portfolio, 2017)
Complex phase transformations in β-stabilised titanium alloys can dramatically change their α and β microstructures, providing tailorability for aerospace or biomaterial applications. Here the authors show that Ti-Nb alloys exhibit giant thermal expansions and identify two new pathways that lead to α phase formation.